THE CREATIVE POTENTIAL TEST AND TECHNOLOGICAL SKILL OF TEACHERS: A NEW PARADIGM OF LEARNING IN THE 21ST CENTURY - Anjarwati, Ani; Az Zahra, Putri Fatimattus (Proceeding of International Conference on Islamic Education (ICIED); Vol 7 No 1 (2022): Proceeding of International Conference on Islamic Education (ICIED), 2022)
The 21st century in the era of the Industrial Revolution 4.0 is marked by changes and technological developments. In the field of education, it must adapt to changes in the era of the industrial revolution 4.0. So it is important for prospective teachers to be able to further develop their creativity in the use of technology for learning. Augmented Reality (AR) based learning can provide a reciprocal relationship between digital objects and real objects. AR is the latest technology that provides convenience to all areas of life, especially in education. The creative potential test in this study aims to make student teacher candidates understand AR-based learning by utilizing the "DEVAR 4D Augmented Reality" application. The research method used in this study is a descriptive quantitative method for descriptions or techniques that are carried out systematically, factually about statements of facts regarding the results of the application of "DEVAR". This research was conducted with descriptive qualitative method. The descriptive research method for this Potential Test Activity obtained very good results, especially for prospective teachers. Prospective teachers are more able to increase their creativity in managing learning.